2022
DOI: 10.3233/shti220163
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Glioma Grading with Deep Learning: A Pilot Study

Abstract: Gliomas are the most common neuroepithelial brain tumors, different by various biological tissue types and prognosis. They could be graded with four levels according to the 2007 WHO classification. The emergence of non-invasive histological and molecular diagnostics for nervous system neoplasms can revolutionize the efficacy and safety of medical care and radically reduce healthcare costs. Our pilot study aimed to evaluate the diagnostic accuracy of deep learning (DL) in subtyping gliomas by WHO grades (I–IV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“… 31 and Decuyper et al., 32 while others defined Ⅲ and Ⅳ(24/54) grades as HGG, such as Danilov et al. 11 and Li et al. 16 Here, our study found that Ⅳ represented HGG in classification was similar to Ⅲ+Ⅳ(SE: 94% vs. 93%; SP:93% vs. 94%; AUC 0.98 vs. 0.98).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“… 31 and Decuyper et al., 32 while others defined Ⅲ and Ⅳ(24/54) grades as HGG, such as Danilov et al. 11 and Li et al. 16 Here, our study found that Ⅳ represented HGG in classification was similar to Ⅲ+Ⅳ(SE: 94% vs. 93%; SP:93% vs. 94%; AUC 0.98 vs. 0.98).…”
Section: Discussionsupporting
confidence: 67%
“…with 1773 images (only 58% SE and 78% SP). 11 Thus, the heterogeneity was still high in the > 130 sample size group, whereas it was decreased in the ≤ 130 group (≤ 130: I 2 = 74.08% in SE and 80.42% in SP; > 130: I 2 = 99.05% in SE and 97.73% in SP). Our study implied that data quality varied enormously in the glioma classification area, which inevitably hindered us from drawing the conclusion of DL.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations